The effect of the noncentral impurity-matrix interaction upon the thermal expansion and polyamorphism of solid CO–C₆₀ solutions at low temperatures - Dolbin, A.V.; Esel’son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Vinnikov, N.A.; Gadd, G.E.; Moricca, S.; Cassidy, D.; Sundqvist, B. (Физика низких температур, 2008)
Orientational glasses with CO molecules occupying 26 and 90% of the octahedral interstitial sites in the C₆₀ lattice have been investigated by the dilatometric method in a temperature interval of 2.5–22 K. At temperatures 4–6 K the glasses undergo a first-order phase transition which is evident from the hysteresis of the thermal expansion and the maxima in the temperature dependences of the linear thermal expansion coefficients α (T), and the thermalization times τ₁(T) of the samples. The effect of the noncentral CO–C₆₀ interaction upon the thermal expansion and the phase transition in these glasses was clarified by comparing the behavior of the properties of the CO–C₆₀ and N₂–C₆₀ solutions.